2015
DOI: 10.1111/jpm.12245
|View full text |Cite
|
Sign up to set email alerts
|

Concept analysis of recovery in mental illness in young adulthood

Abstract: Recovery, as a concept, emerged as a core philosophy of the service user movement that began in the late 1960s and 1970s. Previous reviews on recovery in mental health have presented definitions or a conceptual framework; however, over time it has been open to disparate interpretations. The aim of this paper was to conduct the first concept analysis of mental health recovery in young adulthood within various multidisciplinary contexts. Rodgers's (2000) six-stepped evolutionary method enabled the analysis of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Close investigation of the interviews of PDwS revealed that different mechanisms were used among interviewees to remind them to take medications on time, including putting medication in obvious places, taking medicine at the same time daily, or depending on the primary caregivers to remind them: “….. Previously, my family placed the tablets in my food or juice [ 25 ] , because I refused to take them […]. However, now I take my medication on time [….].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Close investigation of the interviews of PDwS revealed that different mechanisms were used among interviewees to remind them to take medications on time, including putting medication in obvious places, taking medicine at the same time daily, or depending on the primary caregivers to remind them: “….. Previously, my family placed the tablets in my food or juice [ 25 ] , because I refused to take them […]. However, now I take my medication on time [….].…”
Section: Resultsmentioning
confidence: 99%
“…This stigmatisation of mental illness is often associated with a reduction in those affected seeking treatment from a mental health service, engaging in rehabilitation interventions, and adhering to medication [ 23 , 24 ]. Similarly, young people with mental illnesses are often reluctant to seek treatment due to the fear that self-disclosure may be perceived as an individual weakness or may bring shame to one’s family [ 25 ]. In addition, in Arab countries, the distinction between physical and psychological health is not common, and has not been as historically prevalent as in so-called Western Countries.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the experience of failing to meet expectations of self-optimisation might have caused frustration and anger towards the mental health services system. These results indicate that integrating the mental illness into their personal identities and lives in terms of a recovery process is a permanent challenge for transition-age youth [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that attempts to conceptualize a succinct construct of recovery are doomed if they fail to recognize that it is a contested construct. McCauley et al (2015) have highlighted many surrogate terms used in place of recovery by some influential individuals and a number of disciplines. For example, it has been conceptualized as 'the birth of hope' and 'resurrection' (Deegan, 1988, p. 56-57); and 'a journey of the human heart' (Deegan, 1995, p.92).…”
mentioning
confidence: 99%
“…Likewise, the medical meaning has influenced the conceptualization of recovery in the psychiatric and mental health nursing, and the behavioural sciences literature. Consequently, the terms 'recovery' and 'rehabilitation' are often used as substitutes (McCauley et al, 2015).Critics point out that the baffling use of interchangeable terminologies rooted in different philosophies are rarely made explicit (Collier, 2010;Davidson et al 2005). It appears that attempts to conceptualize this complex and multifaceted concept have resulted in a terminological minefield.…”
mentioning
confidence: 99%